Rationale, design and organization of the Second Chinese Cardiac Study (CCS-2): a randomized trial of clopidogrel plus aspirin, and of metoprolol, among patients with suspected acute myocardial infarction. Second Chinese Cardiac Study (CCS-2) Collaborative Group. - Second Chinese Cardiac Study (CCS-2) Collaborative Group (2000)
Assessing combined anti-platelet therapy in suspected acute myocardial infarction Aspirin has been shown to be effective in the emergency treatment of acute myocardial infarction. It irreversibly inhibits platelet cyclo-oxygenase and thereby prevents the formation of the platelet aggregating agent thromboxane A2. Clopidogrel is an anti-platelet agent that acts by a different mechanism, inhibiting adenosine diphosphate-induced platelet aggregation. Simultaneous inhibition of both of these pathways might produce significantly greater anti-platelet effects than inhibition of either alone. The Second Chinese Cardiac Study (CCS-2) will reliably determine whether adding oral clopidogrel to aspirin for up to 4 weeks in hospital after suspected acute myocardial infarction can produce a greater reduction in the risk of major vascular events than can be achieved by giving aspirin alone. In order to be able to detect a further reduction of 10-15%, some 20,000-40,000 patients in over 1000 Chinese hospitals will be randomized. Assessing early beta-blocker therapy in suspected acute myocardial infarction Although over 27,000 patients have been studied previously in randomized trials of short-term beta-blocker therapy in acute myocardial infarction, the reduction in early mortality (513 (3.7%) for beta-blocker therapy deaths versus 586 (4.3%) for control deaths) was only just conventionally significant (P = 0.02) and, overall, the absolute benefits were small in the relatively low-risk patients studied. Although there might be worthwhile benefit in higher risk patients, there is currently little routine use of beta-blocker therapy in acute myocardial infarction. Hence, patients in CCS-2 will also be randomly allocated to receive metoprolol (intravenous then oral) or matching placebo for up to 4 weeks in hospital in a 2 x 2 factorial design. Such a design allows all patients to contribute fully to assessment of the separate effects of the anti-platelet regimen and the beta-blocker (without any material effect on study cost or sample size requirements) whilst also providing information about their combined effects. A streamlined trial in a wide range of patients In order to randomize 20,000-40,000 patients, the design of CCS-2 has been streamlined: data collection and other extra work for collaborators is minimal, allowing busy hospitals to take part easily. All patients presenting within 24 h of the onset of suspected acute myocardial infarction are eligible for the study provided they have a definite ECG abnormality and are not persistently hypotensive, and provided the doctor responsible considers there to be no clear indication for or contraindication to either of the trial treatments. Apart from administration of the trial treatments, all other aspects of individual patient management are entirely at the discretion of the doctor responsible. By including many different types of patient from many different types of hospital, with wide variation in ancillary management, the CCS-2 results will be of direct clinical relevance to the heterogeneous realities of future clinical practice. The trial began in July 1999 and is expected to be completed by the year 2003.